2020
DOI: 10.1177/2325967120922554
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Overuse-Related Structural Abnormalities in the Lumbar Spine of Youth Competitive Alpine Skiers: A Cross-sectional MRI Study in 108 Athletes

Abstract: Background: Alpine ski racing is known as a sport with unfavorable spinal loads and high rates of back overuse injuries at the elite level. However, little is known about overuse-related structural abnormalities occurring in the spine of youth athletes. Purpose: To describe the prevalence of abnormal magnetic resonance imaging (MRI) findings in the lumbar spine of youth competitive alpine skiers within the U16 category (under 16 years) with respect to sex, height growth, multifidus size, increasing age, and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
0
22
1
Order By: Relevance
“…Despite these plausible sports-related adverse loading patterns, only a few studies, however, have investigated the occurrence of lower back complaints in competitive alpine skiers. Moreover, due to focusing on a different age group and reporting other time prevalence measures or absolute injury rates, most of them are not directly comparable to the results of the current study [3,4,6,8,11]. The only study directly comparable to our investigation reported similar magnitudes of current low back pain (67.0%) in ski high school athletes aged 15-19 years [30].…”
Section: Prevalence Of Lower Back Complaints With Respect To Sex Catcontrasting
confidence: 71%
See 2 more Smart Citations
“…Despite these plausible sports-related adverse loading patterns, only a few studies, however, have investigated the occurrence of lower back complaints in competitive alpine skiers. Moreover, due to focusing on a different age group and reporting other time prevalence measures or absolute injury rates, most of them are not directly comparable to the results of the current study [3,4,6,8,11]. The only study directly comparable to our investigation reported similar magnitudes of current low back pain (67.0%) in ski high school athletes aged 15-19 years [30].…”
Section: Prevalence Of Lower Back Complaints With Respect To Sex Catcontrasting
confidence: 71%
“…Specifically, degenerative disc changes were observed to be more prevalent in adolescent competitive alpine skiers than in age-matched controls [10]. Moreover, a recent study found such disc degenerations (particularly disc dehydration and disc protrusion) to be significantly more prevalent in symptomatic than in asymptomatic athletes [11]. However, little is known about the prevalence of lower back complaints in adolescent skiers with respect to severity (i.e., intensity and disability).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the ACSA of multifidus muscle [ 108 111 ] and the ratio between the ACSAs of the multifidus and quadratus lumborum muscles [ 111 ] were related to the occurrence of lower extremities injury both in the pre-season and playing season. In a recent study conducted in young competitive alpine skiers, a smaller lumbar multifidus ACSA (assessed by MRI) was related to a higher occurrence of disc protrusions and end plate alterations [ 112 ]. Moreover, bilateral muscle differences in rectus femoris and VL ACSAs may be associated with games missed because of lower extremity injury in professional basketball players [ 38 ].…”
Section: Fields Of Application In Elite Sportsmentioning
confidence: 99%
“…[9][10][11] A major concern pertains to youth skiers around the growth spurt, whose bodies are still maturing and, therefore, are especially sensitive to unfavourable loads. 11,12 Moreover, in under 16 years old (U16) skiers, overuse injuries revealed to be more frequent in females than in males. 9 In skiing, up to 1.75 times the body weight can act on each leg, 13 and the knee joint is inevitably subjected to extreme kinematics, including high degrees of flexion and valgus.…”
Section: Introductionmentioning
confidence: 99%